2018
DOI: 10.22159/ijcpr.2018v10i1.24405
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin: A Magical Therapy for Healthy Heart

Abstract: Relaxin (a peptide hormone) has emerged as a cardio protective agent and plays a vital role in normal cardiac function. By activation a complex network of signalling cascade, relaxin is responsible for creating a healthy environment for heart functioning. Under pathological conditions, such as cardiomyopathy and heart failure, the expression level of relaxin is increased dramatically to protect the heart. By promoting angiogenesis, vasodilatation, improving ischemia/reperfusion injury and remodeling, relaxin h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…were unearthed (8)(9)(10)(11). Humans express three types of relaxins (relaxin 1, relaxin 2, and relaxin 3), and each performs a unique role (12,13). It has been reported that relaxin 2 (RLXH2) gets overexpressed in different cancers and aids in cell proliferation, metastasis and invasiveness (14,15).…”
mentioning
confidence: 99%
“…were unearthed (8)(9)(10)(11). Humans express three types of relaxins (relaxin 1, relaxin 2, and relaxin 3), and each performs a unique role (12,13). It has been reported that relaxin 2 (RLXH2) gets overexpressed in different cancers and aids in cell proliferation, metastasis and invasiveness (14,15).…”
mentioning
confidence: 99%